Impacts de l’utilisation des eaux polluées en agriculture urbaine sur la qualité de la nappe de Dakar (Sénégal) - M. L. Ndiaye; H.-R. Pfeifer; S. Niang; Y. Dieng; M. Tonolla; R. Peduzzi (VertigO)
In Dakar capital city of Senegal, the urban agriculture is in high expansion. Since the progressive increase of salinity in the local groundwater (Céanes water), raw wastewater is used to water the crops. The objective of this study is to assess chemical and microbiological quality of the groundwater underlying the irrigated plots and to identify the sources of pollution. This work was carried out in the sites of Pikine and Patte d’Oie in Dakar Senegal.Chemical analysis of irrigation water showed that in Pikine, the conductivity of Céanes water was higher (4822±2411 µS cm-1) than those of the wastewater (3579±1242 µS cm-1 ; p